2014
DOI: 10.1017/s0031182014000730
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the southern European border ofEchinococcus multilocularisin the Alps: evidence thatMicrotus arvalisis a limiting factor

Abstract: S U M M A R YThe known range of the zoonotic fox tapeworm Echinococcus multilocularis has expanded since the 1990s, and today this parasite is recorded in higher abundances throughout large parts of Europe. This phenomenon is mostly attributed to the increasing European fox populations and their invasion of urban habitats. However, these factors alone are insufficient to explain the heterogeneous distribution of the parasite in Europe. Here, we analysed the spatial interrelationship of E. multilocularis with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 59 publications
1
36
0
Order By: Relevance
“…Some authors have associated the variation in prevalence to the variations in host life-history traits (mostly age structure of populations) and/or in environmental parameters, such as climate, landscape characteristics or geographical location (for recent reviews see Atkinson et al, 2013;Otero-Abad and Torgerson, 2013). For example, a number of surveys on regional or national scales have identified a high spatial heterogeneity in the prevalence of the parasite in red fox (V. vulpes) populations (Miterpakova et al, 2006;Combes et al, 2012;Guerra et al, 2014). In a recent screening in the north-eastern half of France covering an area of 240,000 km 2 , Combes et al (2012) showed prevalence variation from more than 60% to less than 10% within only some tens of kilometres.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have associated the variation in prevalence to the variations in host life-history traits (mostly age structure of populations) and/or in environmental parameters, such as climate, landscape characteristics or geographical location (for recent reviews see Atkinson et al, 2013;Otero-Abad and Torgerson, 2013). For example, a number of surveys on regional or national scales have identified a high spatial heterogeneity in the prevalence of the parasite in red fox (V. vulpes) populations (Miterpakova et al, 2006;Combes et al, 2012;Guerra et al, 2014). In a recent screening in the north-eastern half of France covering an area of 240,000 km 2 , Combes et al (2012) showed prevalence variation from more than 60% to less than 10% within only some tens of kilometres.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it has been proposed that small scale variations in the distribution, abundance and population dynamics of intermediate hosts (e.g. Guerra et al, 2014) and interactions between host populations via predator-prey relationship could play a critical role in the transmission intensity of the parasite . On a more local scale, the transmission of the parasite's eggs to intermediate hosts is governed by the distribution of the definitive host's faeces in the environment and the micro-climatic conditions controlling egg survival (Giraudoux et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Confirmation of this could be achieved after dietary analysis of foxes, such as done to assess the Southern European border of E. multilocularis (Guerra et al, 2014). The importance of hares as prey species for the red fox in Central Europe has already been documented in multiple studies (Knauer et al, 2010;Zellweger-Fischer et al, 2011;Schmidt et al, 2004).…”
Section: (Discussion)mentioning
confidence: 87%
“…In Switzerland, the transmission dynamics of E. multilocularis depends primarily upon the ecosystem of red foxes (Vulpes vulpes) and small mammal intermediate hosts such as Arvicola terrestris and Microtus arvalis (Hegglin et al, 2015;Guerra et al, 2014). Red foxes are high prevalence hosts of E. multilocularis in Switzerland (Lewis et al, 2014), resulting in a high environmental contamination rate with E. multilocularis eggs.…”
Section: (Discussion)mentioning
confidence: 99%
“…Determinants for the distribution of E. mutilocularis vary spatially and temporally. These reflect the influence of local ecological assemblages as indicated by the preponderance of infections in coyote from western Canada , or by the apparent limitations in distribution in western Europe that may reflect associations with specific vole intermediate hosts (Microtus arvalis) (Guerra et al, 2014). Interestingly, a focus of E. multilocularis was established on Svalbard following the inadvertent introduction of a suitable intermediate host, the sibling vole (Microtus rossiaemeridionalis), which enabled the completion of the life cycle (Henttonen et al, 2001).…”
Section: Complexity Among Species Of Echinococcusmentioning
confidence: 99%